Geodesics of Hayward black hole surrounded by quintessence - Cabrera Munguia, Roberto Ivan (2021)
Basing on the ideas used by Kiselev, we study the Hayward black hole surrounded by quintessence. The values critical of mass and the normalization factor are obtained. We also described the horizons and the extremal condition of the Hayward black hole surrounded by quintessence. By setting for the quintessence state parameter at the particular case of ω = − 2/3 , we study the effective potential, and we analyzed in detail 3 the null geodesics for different energies as well as the behavior of horizons. Finally, the shadow of the black hole is explored.